(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
In this article, we present the students of junior high school based on spiritual and moral traditions, customs, general human values, intellectual, moral, free thinking and physical personal development that allows him to fully reveal his abilities. principles are briefly stated.